Constructivist and socio-cognitive applications in second and foreign language teaching and learning - Cundar-Ruano, Adriana Ximena (Dominio de las Ciencias, 2021)
This article covers practical applications of two of the most outstanding learning theories that have contributed to foreign language teaching and learning. This paper deems Constructivism and Socio-cognitive theories as alternative approaches to traditional objectivist practices that have been deeply rooted in English as foreign language classrooms for decades. Vygotsky’s constructivist principles of scaffolding in the zone of proximal development (ZPD) and Bandura’s socio-cognitive notions of self-regulation are discussed as concepts teachers should examine when contemplating alternatives to enhance and broaden their teaching perspectives. A significant portion of this paper deals with educational applications and foreign language research from Constructivism and Socio-cognitive theories. Likewise, the several influences on foreign language learners' learning and performance are discussed regarding the ZPD and self-regulation. This analysis reckons that although the switch to constructivist and socio-cognitive practices in foreign language teaching may imply some teachers' challenges, the benefits exceed the possible difficulties they may encounter. The paper calls for more detailed research on applications of constructivism and socio-cognitive theories in the English as a foreign language classroom.